Construction of submicron-sized LiFe0.4Mn0.6PO4/C enwrapped into graphene framework for advanced Li-storage. (November 2020) - Wu, Kaipeng; Yin, Shan; Wang, Shen; Zhu, Jinliang; Yao, Weitang
Abstract: LiFe1-x Mnx PO4, which combines the advantages of excellent rate capability of LiFePO4 and high operation voltage of LiMnPO4, is widely studied as a promising cathode for the purpose of facilitating its electronic conductivity and Li-ion mobility. Herein, a double-carbon co-modified strategy is introduced to design and construct carbon-coated LiFe0.4 Mn0.6 PO4 enwrapped into 3D graphene framework (LiFe0.4 Mn0.6 PO4 /C/rGO), in which a novel Fe0.4 Mn0.6 C2 O4 ·2H2 O/GO precursor is creatively introduced and synthesized via fast in-situ coprecipitation without any pH regulator. In the LiFe0.4 Mn0.6 PO4 /C/rGO architecture, well dispersive LiFe0.4 Mn0.6 PO4 particles with submicron-size are uniformly coated by a conductive carbon layer to form LiFe0.4 Mn0.6 PO4 /C, which are tightly anchored on and enwrapped into 3D graphene framework, guaranteeing sufficient "face-to-face" intimate contact between these three components. Benefiting from synergetic contributions from the well-designed 3D conductive network, fast Li-ion diffusion path, and unique structure for electrolyte penetration, the integrated LiFe0.4 Mn0.6 PO4 /C/rGO yields high discharge capacity of 159.5 mAh·g −1 at 0.05C, superior rate capacity of 118.7 mAh·g −1 at 10C, and durable capacity retention of 96.4% after 200 cycles at 2 C. This proposed efficiency strategy can also be extended to other advanced cathodes for high-energy LIBs. Graphical abstract: Image 1